Investigation of diamond electrodes for photo‐electrochemistry. Issue 10 (11th July 2014) - Bechter, Jonathan; Pietzka, Carsten; Petkov, Christo; Reintanz, Philipp; Siemeling, Ulrich; Popov, Cyril; Pasquarelli, Alberto
Abstract : Boron doped diamond (BDD) shows high chemical stability in contact with a liquid phase even under extreme pH conditions, high electrochemical activity, and allows very stable covalent functionalization on O‐ or N‐terminated surfaces. It is therefore an excellent electrode material for many applications such as analytics, biosensors, and purification. Furthermore, the electrodes can be covalently functionalized with photo‐sensitive dyes to generate photo currents. However, the energetic conditions and charge transfer mechanisms are not fully known and therefore have been investigated in this work. The focus was set on the energy band diagrams of nanocrystalline diamond (NCD) layers, especially on the flat‐band potential V F and the band‐bending ϕ B in the space charge layer, for both O‐ and N‐terminated surfaces, and the charge transfer mechanisms at the semiconductor/electrolyte phase‐boundary, with or without electro‐active organic dyes, such as manganese phthalocyanine. For this study NCD samples were grown by hot filament chemical vapor deposition (HFCVD) with a boron doping density N A ranging between 5.8 and 9.6 × 10 20  cm −3 . The pristine surface was then processed by oxygen or ammonia plasma to modify the termination to O and NH2, respectively. After that a series of Mott–Schottky plots was measured for both terminations at several frequencies spanning from 3 Hz to 10 kHz and in two different electrolytes, namely 0.1 M H2 SO4 and 0.1 M KCl. The results showed nearly the same flat‐band potential for both surface terminations, but a remarkable difference in the band‐bending. The latter is most probably responsible for the better photoelectrical conversion observed in N‐terminated NCD samples. The open‐circuit potential (OCP) and chronoamperometric measurements performed after covalent functionalization of the samples with the color dyes revealed that only the N‐terminated material delivered a measurable photocurrent. Although the global efficiency of the photoelectric conversion was low, these initial results show that by optimized selection of materials and modification technologies providing a proper match of the energy levels at all charge transfer steps, a higher energy output could be achieved.